4th Polish Mining Congress-Session: Human and environment facing the challenges of mining. (July 2018) - Unknown
Abstract : Preface Dear Ladies and Gentlemen, Between 20 th and 22 th of November 2017 in Cracow (Poland) took place the 4 th Polish Mining Congress. Congress was held under the slogan: „Mineral resources in Poland's economic strategy – how to mine, how to acquire, how to save in the era of sustainable development?"